Rural Development in Nepal: A Historical Perspective - Gautam, Murari Krishna (Interdisciplinary Journal of Management and Social Sciences, 2020)
Least developed country like Nepal, the development programmes and policies are key components for the livelihood of rural poor and sustainable development. This paper is tries to carry out the historical perspectives of rural development in Nepal. The rural development policies and programmes are also essential for the national development. But the implemented policies and programmes for rural development by the governments of different time periods in Nepal are not sufficient as rural Nepal needed. It is strongly required to launch the agriculture based policies and programmes for rural Nepal. Using secondary information, the paper analyzes the major provision for the rural development in the country. Moreover, the rural development sector needs to develop some more popular and specific development policies and programmes and models of development.